Composition for preparing polyethylene grafted polylactic acid copolymer and preparation method of polyethylene grafted polylactic acid copolymer
Patent Information
- Application Number
- CN202411823768.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
AI Technical Summary
Due to its inherent brittleness and poor thermal stability, polylactic acid limits its application in a wider field, and existing modification methods are difficult to effectively improve its toughening performance and reduce production costs.
By preparing polyethylene grafted polylactic acid copolymer, the polyethylene-vinyl alcohol copolymer is used as an initiator to initiate ring-opening polymerization of small molecule lactide monomer to form polyethylene grafted polylactic acid copolymer as a toughening modifier for polylactic acid.
Significant toughening modification of polylactic acid is achieved, the mechanical properties of the material are improved, the production costs are reduced, and the environmentally friendly properties of the material are maintained.
Smart Images

Figure HDA0005184278820000011 
Figure HDA0005184278820000012 
Figure HDA0005184278820000021
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of polymer materials, and specifically relates to a composition for preparing a polyethylene grafted polylactic acid copolymer and a method for preparing the polyethylene grafted polylactic acid copolymer. Background Art
[0002] As a biodegradable plastic, polylactic acid (PLA) has been widely used in packaging, medical treatment, 3D printing and other fields due to its excellent environmental performance and plasticity. However, its inherent brittleness and poor thermal stability limit its application in a wider range of fields. Although some progress has been made, the research on toughening and modification of PLA still faces many challenges. For example, how to improve the modification effect, reduce production costs, and improve environmental performance still need to be further resolved.
[0003] Graft copolymers have become a polymer material with broad development and application prospects due to their unique topological chain structure and diverse properties. Graft copolymers can be used as toughening modifiers. Researchers have found that by designing their structure, they can achieve the dual effects of elastomers and compatibilizers. This allows a significant toughening effect to be achieved even when a small amount of toughening agent is added, thereby improving the brittleness of the material and enhancing its practical value. Graft copolymers containing PLA side chains have a unique chain structure and good compatibility with the PLA matrix. They present a nanoscale dispersion scale in the PLA matrix, and the suspended side chains can produce effective chain entanglement and a good interface with the matrix molecular chain segments, thereby bringing about efficient stress transfer. Often, they can have a significant toughening effect when added in small amounts. Therefore, the scheme of organically combining recyclable polymer materials with excellent performance and low cost with degradable materials such as PLA to achieve modification has broad application prospects. Summary of the invention
[0004] The purpose of the present application is to provide a composition for preparing a polyethylene grafted polylactic acid copolymer and a method for preparing the polyethylene grafted polylactic acid copolymer.
[0005] In a first aspect, the present application provides a composition for preparing a polyethylene-grafted polylactic acid copolymer, which comprises a polyethylene-vinyl alcohol copolymer, lactide, a catalyst and a solvent.
[0006] In some embodiments, the number average molecular weight of the polyethylene-vinyl alcohol copolymer is 10000-60000, for example, 11000, 13000, 15000, 17000, 19000, 20000, 21000, 23000, 25000, 27000, 29000, 30000, 31000, 33000, 35000, 37000, 39000, 40000, 41000, 43000, 45000, 47000, 49000, 50000, 51000, 53000, 55000, 57000, 59000 or any value therebetween. In some embodiments, the number average molecular weight of the polyethylene-vinyl alcohol copolymer is 12000-54000.
[0007] In some embodiments, the mass ratio of lactide to polyethylene-vinyl alcohol copolymer is 1:0.1-1:5, for example, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.8 In some embodiments, the mass ratio of lactide to polyethylene-vinyl alcohol copolymer is 1:0.2-1:2. In some embodiments, the mass ratio of lactide to polyethylene-vinyl alcohol copolymer is 1:0.25-1:0.5.
[0008] In some embodiments, the mass ratio of the lactide to the polyethylene-vinyl alcohol copolymer is 1:5-10:1, preferably 1:2-5:1.
[0009] In some embodiments, the mole percentage of alcoholic hydroxyl groups in the polyethylene-vinyl alcohol copolymer is 3%-30%, for example, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or any value therebetween. In some embodiments, the mole percentage of alcoholic hydroxyl groups is 5%-25%. In some embodiments, the mole percentage of alcoholic hydroxyl groups is 7%-18%.
[0010] In some embodiments, the catalyst is selected from one or more of stannous octoate, tributyl methoxystannane, dibutyl tin octoate, tetraphenyl tin, triethoxyaluminum, dibutyl zinc, triethyl cadmium and triethyl aluminum.
[0011] In some embodiments, the solvent is selected from one or more of toluene, xylene, chlorotoluene, dichloromethane, dioxane and tetrahydrofuran.
[0012] In a second aspect, the present application provides a method for preparing a polyethylene-grafted polylactic acid copolymer, which comprises reacting a polyethylene-vinyl alcohol copolymer and lactide in a solvent in the presence of a catalyst.
[0013] The present application uses polyethylene-vinyl alcohol copolymer as an initiator to initiate the ring-opening polymerization of small molecule lactide monomers. The operation is simple and easy to master. The introduction of polyethylene flexible chain segments in the polyethylene-vinyl alcohol copolymer helps to improve the mechanical properties, thereby achieving toughening modification of polylactic acid.
[0014] In some embodiments, the number average molecular weight of the polyethylene-vinyl alcohol copolymer is 10000-60000, for example, 11000, 13000, 15000, 17000, 19000, 20000, 21000, 23000, 25000, 27000, 29000, 30000, 31000, 33000, 35000, 37000, 39000, 40000, 41000, 43000, 45000, 47000, 49000, 50000, 51000, 53000, 55000, 57000, 59000 or any value therebetween. In some embodiments, the number average molecular weight of the polyethylene-vinyl alcohol copolymer is 12000-54000.
[0015] In some embodiments, the mass ratio of lactide to polyethylene-vinyl alcohol copolymer is 1:0.1-1:5, for example, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.8 In some embodiments, the mass ratio of lactide to polyethylene-vinyl alcohol copolymer is 1:0.2-1:2. In some embodiments, the mass ratio of lactide to polyethylene-vinyl alcohol copolymer is 1:0.25-1:0.5.
[0016] In some embodiments, the mass ratio of the lactide to the polyethylene-vinyl alcohol copolymer is 1:5-10:1, preferably 1:2-5:1.
[0017] In some embodiments, the mole percentage of alcoholic hydroxyl groups in the polyethylene-vinyl alcohol copolymer is 3%-30%, for example, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or any value therebetween. In some embodiments, the mole percentage of alcoholic hydroxyl groups is 5%-25%. In some embodiments, the mole percentage of alcoholic hydroxyl groups is 7%-18%.
[0018] In some embodiments, the catalyst is selected from one or more of stannous octoate, tributyl methoxystannane, dibutyl tin octoate, tetraphenyl tin, triethoxyaluminum, dibutyl zinc, triethyl cadmium and triethyl aluminum.
[0019] In some embodiments, the solvent is selected from one or more of toluene, xylene, chlorotoluene, dichloromethane, dioxane and tetrahydrofuran.
[0020] In some embodiments, the reaction temperature is 50°C-150°C, such as 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or any value therebetween. In some embodiments, the reaction temperature is 90°C-110°C.
[0021] In some embodiments, the reaction time is 2h-48h, for example, 4h, 8h, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h or any value therebetween. In some embodiments, the reaction time is 16h-24h.
[0022] In some embodiments, the reaction is performed under an inert atmosphere, such as a nitrogen atmosphere.
[0023] In some embodiments, the method for preparing the polyethylene grafted polylactic acid copolymer provided in the present application comprises the following specific steps:
[0024] Add polyethylene-vinyl alcohol copolymer, lactide, catalyst and solvent into a dry reactor, stir and react at 50-150° C. for 2-48 hours under an inert atmosphere, terminate the reaction, and obtain the target product through precipitation, filtration, dialysis and drying.
[0025] In a third aspect, the present application provides a polyethylene grafted polylactic acid copolymer prepared by the preparation method described in the second aspect.
[0026] In some embodiments, the polyethylene grafted polylactic acid copolymer has a number average molecular weight of 40,000-100,000, for example, 45,000, 50,000, 55,000, 60,000, 65,000, 70,000, 75,000, 80,000, 85,000, 90,000 or 95,000.
[0027] In some embodiments, the elongation at break of the polyethylene-grafted polylactic acid copolymer is greater than or equal to 70%, for example, 100%, 150%, 200%, 300%, 350%, 400% or any value therebetween.
[0028] In a fourth aspect, the present application provides the use of the polyethylene grafted polylactic acid copolymer described in the third aspect as a polylactic acid toughening modifier.
[0029] Beneficial technical effects of this application:
[0030] 1. The raw materials for the preparation method of the polyethylene grafted polylactic acid grafted copolymer provided in the present application are widely available and inexpensive.
[0031] 2. The preparation method of the polyethylene grafted polylactic acid grafted copolymer provided in the present application uses polyethylene-vinyl alcohol copolymer as an initiator to initiate the ring-opening polymerization of small molecule lactide monomers, and the operation is simple and easy to master.
[0032] 3. The polyethylene grafted polylactic acid grafted copolymer provided in this application is a new polylactic acid toughening modifier. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the infrared spectrum of the polyethylene grafted polylactic acid copolymer prepared in Example 1.
[0034] Figure 2 This is the infrared spectrum of the polyethylene grafted polylactic acid copolymer prepared in Example 2.
[0035] Figure 3 This is the infrared spectrum of the polyethylene grafted polylactic acid copolymer prepared in Example 3.
[0036] Figure 4 This is the infrared spectrum of the polyethylene grafted polylactic acid copolymer prepared in Example 4. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the present application clearer, the present application is further described in detail below in conjunction with the embodiments. The specific embodiments described herein are only used to explain the present application and are not intended to constitute any limitation to the present application. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0038] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0039] The present application will be described in detail below through examples and comparative examples.
[0040] Example 1
[0041] Preparation of Polyethylene Grafted Polylactic Acid
[0042] 1.0 g of polyethylene-vinyl alcohol copolymer (number average molecular weight of 24,000, hydroxyl molar content of 18%), 2.0 g of lactide and 0.002 g of stannous octoate were added to a dry reactor, and then 100 mL of toluene was added. The reaction was carried out at 95° C. for 24 h under a nitrogen inert atmosphere, and the reaction was terminated. The reaction product was precipitated, filtered, dialyzed, and dried to obtain the target product.
[0043] The target product was subjected to infrared spectroscopy analysis test (specific results are shown in the attached Figure 1 ), gel permeation chromatography analysis test (specific results are shown in Table 1) and mechanical properties analysis test (specific results are shown in Table 1).
[0044] Example 2
[0045] Preparation of Polyethylene Grafted Polylactic Acid
[0046] 1.0 g of polyethylene-vinyl alcohol copolymer (number average molecular weight of 24,000, hydroxyl molar content of 18%), 3.0 g of lactide and 0.003 g of stannous octoate were added to a dry reactor, and then 100 mL of toluene was added. The reaction was carried out at 95° C. for 24 h under a nitrogen inert atmosphere, and the reaction was terminated. The reaction product was precipitated, filtered, dialyzed, and dried to obtain the target product.
[0047] The target product was subjected to infrared spectroscopy analysis test (specific results are shown in the attached Figure 2 ), gel permeation chromatography analysis test (specific results are shown in Table 1) and mechanical properties analysis test (specific results are shown in Table 1).
[0048] Example 3
[0049] Preparation of Polyethylene Grafted Polylactic Acid
[0050] 1.0 g of polyethylene-vinyl alcohol copolymer (number average molecular weight of 24,000, hydroxyl molar content of 18%), 4.0 g of lactide and 0.004 g of stannous octoate were added to a dry reactor, and then 100 mL of toluene was added. The reaction was carried out at 95° C. for 24 h under a nitrogen inert atmosphere, and the reaction was terminated. The reaction product was precipitated, filtered, dialyzed, and dried to obtain the target product.
[0051] The target product was subjected to infrared spectroscopy analysis test (specific results are shown in the attached Figure 3 ), gel permeation chromatography analysis test (specific results are shown in Table 1) and mechanical properties analysis test (specific results are shown in Table 1).
[0052] Example 4
[0053] Preparation of Polyethylene Grafted Polylactic Acid
[0054] 1.0 g of polyethylene-vinyl alcohol copolymer (number average molecular weight of 24,000, hydroxyl molar content of 18%), 5.0 g of lactide and 0.005 g of stannous octoate were added to a dry reactor, and then 100 mL of toluene was added. The reaction was carried out at 95° C. for 24 h under a nitrogen inert atmosphere, and the reaction was terminated. The reaction product was precipitated, filtered, dialyzed, and dried to obtain the target product.
[0055] The target product was subjected to infrared spectroscopy analysis test (specific results are shown in the attached Figure 4 ), gel permeation chromatography analysis test (specific results are shown in Table 1) and mechanical properties analysis test (specific results are shown in Table 1).
[0056] Comparative Example 1
[0057] Preparation of polylactic acid
[0058] 1.0 g of polyethylene glycol (number average molecular weight of 800), 75.0 g of lactide and 0.025 g of stannous octoate were added to a dry reactor, and then 250 mL of toluene was added, and the reaction was carried out at 150° C. for 8 h under a nitrogen inert atmosphere, and the reaction was terminated. The reaction product was precipitated, filtered, dialyzed and dried to obtain the target product.
[0059] The target product was subjected to gel permeation chromatography analysis test (specific results are shown in Table 1) and mechanical properties analysis test (specific results are shown in Table 1).
[0060] Table 1
[0061] serial number Number average molecular weight / Da Tensile strength / MPa Elongation at break / % Example 1 45000 17.05 75.64 Example 2 64000 9.44 314.51 Example 3 82000 11.48 242.67 Example 4 98000 14.65 212.64 Comparative Example 1 68000 40.52 2.99
[0062] The preferred embodiments of the present application are described in detail above, but the present application is not limited thereto. Within the technical concept of the present application, the technical solution of the present application can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed in the present application and belong to the protection scope of the present application.
Claims
1. A composition for preparing a polyethylene-grafted polylactic acid copolymer, comprising a polyethylene-vinyl alcohol copolymer, lactide, a catalyst and a solvent.
2. The composition according to claim 1, characterized in that The number average molecular weight of the polyethylene-vinyl alcohol copolymer is 10,000-60,000, preferably 12,000-54,000; and / or The mass ratio of the lactide to the polyethylene-vinyl alcohol copolymer is 1:0.1-1:5, preferably 1:0.2-1:2 and more preferably 1:0.25-1:0.
5.
3. The composition according to claim 1 or 2, characterized in that The molar percentage of alcoholic hydroxyl groups in the polyethylene-vinyl alcohol copolymer is 3%-30%, preferably 5%-25%, and more preferably 7%-18%.
4. The composition according to any one of claims 1 to 3, characterized in that The catalyst is selected from one or more of stannous octoate, tributyl methoxystannane, dibutyl tin octoate, tetraphenyl tin, triethoxyaluminum, dibutyl zinc, triethyl cadmium and triethyl aluminum; and / or The solvent is selected from one or more of toluene, xylene, chlorotoluene, dichloromethane, dioxane and tetrahydrofuran.
5. A method for preparing a polyethylene-grafted polylactic acid copolymer, comprising reacting a polyethylene-vinyl alcohol copolymer and lactide in a solvent in the presence of a catalyst.
6. The preparation method according to claim 5, characterized in that: The number average molecular weight of the polyethylene-vinyl alcohol copolymer is 10,000-60,000, preferably 12,000-54,000; and / or The mass ratio of the lactide to the polyethylene-vinyl alcohol copolymer is 1:0.1-1:5, preferably 1:0.2-1:2, and more preferably 1:0.25-1:0.
5.
7. The preparation method according to claim 5 or 6, characterized in that: The molar percentage of alcoholic hydroxyl groups in the polyethylene-vinyl alcohol copolymer is 3%-30%, preferably 5%-25%, and more preferably 7%-18%.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The catalyst is selected from one or more of stannous octoate, tributyl methoxystannane, dibutyl tin octoate, tetraphenyl tin, triethoxyaluminum, dibutyl zinc, triethyl cadmium and triethyl aluminum; and / or The solvent is selected from one or more of toluene, xylene, chlorotoluene, dichloromethane, dioxane and tetrahydrofuran; and / or The reaction temperature is 50°C-150°C, preferably 90°C-110°C; and / or The reaction time is 2h-48h, preferably 16h-24h.
9. A polyethylene-grafted polylactic acid copolymer prepared by the preparation method according to any one of claims 5 to 8.
10. Use of the polyethylene grafted polylactic acid copolymer according to claim 9 as a polylactic acid toughening modifier.
Citation Information
Patent Citations
Method for improving water resisting performance of polyvinyl alcohol film from polycaprolactone and polylactic acid
CN103865091A
Multi-layer heat-resistant and high-transparency degradable polylactic acid-based film
CN113427867A
Polylactic acid-based environment-friendly agricultural mulching film and preparation method thereof
CN113524831A
Method for preparing polylactic acid-polyvinyl alcohol grafted copolymer
CN115926122A
Comb-shaped graft copolymer as well as preparation and application thereof
CN118047953A